2022
DOI: 10.1088/1361-6463/ac55c1
|View full text |Cite
|
Sign up to set email alerts
|

CO2 dissociation in a packed bed DBD reactor: effect of streamer discharge

Abstract: Non-thermal plasma catalysis, as a special heterogeneous catalytic reaction, needs to consider both gas discharge and catalytic reaction. Packed bed dielectric barrier discharge (PB-DBD) is widely used in non-thermal plasma catalysis, but the exact control principle of gas discharge, especially streamer discharge, is not clear. In this study, therefore, the orderly arranged dielectric rods were packed in the discharge gap of PB-DBD, and the streamer discharge behaviors were controlled by adjusting their diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 37 publications
(54 reference statements)
0
30
0
Order By: Relevance
“…The filamentary nature of the discharge in a loosely PB-DBD and the influence of the streamers in the conversion efficiency has been recently demonstrated experimentally in Ref. [9]. In this reference, the authors show that a DBD reactor packed with simple, high-permittivity, dielectric rods (no active material) can significantly enhance the CO 2 conversion and efficiency.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…The filamentary nature of the discharge in a loosely PB-DBD and the influence of the streamers in the conversion efficiency has been recently demonstrated experimentally in Ref. [9]. In this reference, the authors show that a DBD reactor packed with simple, high-permittivity, dielectric rods (no active material) can significantly enhance the CO 2 conversion and efficiency.…”
Section: Introductionmentioning
confidence: 91%
“…The simulated geometry corresponds to the experimental study of Ref. [9] and the 12 dielectric rods case. It consists of a coaxial DBD reactor, with a ground rod electrode at its center and a highvoltage electrode wrapped around a quartz tube with dielectric permittivity of 4.5.…”
Section: Modeling and Computational Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dielectric properties of the reactor material were shown to impact conversion in both tubular and planar DBD reactors [21,22]. Zhang et al found that the CO 2 conversion increased to 18% in a packed bed DBD reactor as the shorter distance between the glass particles enhanced the electric eld [23].…”
Section: Introductionmentioning
confidence: 99%